Voices of talent search sixth grade TRIO students: a case study of their program experiences - Schmidt, Laurie Ann, author; Lehmann, Jean P., advisor; Davies, Timothy Gray, committee member; Hall, Bruce, committee member; Carlson, Laurie A., committee member (Colorado State University. Libraries, 2004)
This study examined the question: How do at-risk sixth grade students in Northwest Iowa experience the Educational Talent Search Success for Sixth TRIO program? Talent Search programs are a pre-college intervention program for at-risk students. If educators are to reach these at-risk students, they must begin by listening carefully to their voices. Currently, there appears to be few documents that capture the voices and experiences of at-risk sixth grade students. This case study captures the voices of twelve students who were enrolled in the Educational Talent Search Success for Sixth program from January 2002 - March 2002. The purpose of this qualitative case study was to collect and document the experiences of sixth grade, at-risk youth enrolled in the Educational Talent Search program in Northwest Iowa. Through systematic data gathering and analysis procedures, the researcher sought to determine how students experienced the program. This study is designed to empower at-risk Success for Sixth students by carefully listening to their voices and by hearing their stories of how they experienced the program. Results from this study revealed that there were two core themes: Relationships, and Identities, and five support themes: Friendships, Peer-pressure, Self-esteem, Self-confidence, and Activities. These themes provide the framework to understand how at-risk middle school students experience an after school program from their perspective. Perhaps the most important implication for this study is the fact that at-risk middle school students are rarely listened to or empowered in their educational endeavors. These children face numerous hidden obstacles that may permanently scar them if caring educators do not address them. Unless they are given the chance to voice their frustrations, many at-risk students suffer in silence and isolation. It is important to measure these core and support themes in a quantitative format with instruments that are both valid and reliable measures of these themes for future information. Further, it is essential to ascertain if students from different socioeconomic status and backgrounds report similar themes. More research needs to be done to further listen to the voices of our at-risk youth.
Keywords: educational sociology; elementary education